1960
DOI: 10.1085/jgp.44.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Carrier Function of Phosphatidic Acid in Sodium Transport

Abstract: Incubation of slices of the salt gland of the albatross with acetylcholine, which is the physiological secretogogue for this tissue, led to a 13-fold increase in the rate of incorporation of p3~ into phosphatidic acid and a 3-fold increase in the incorporation of p82 and inositol-2-H 3 into phosphoinositide. The incorporation of p~2 into phosphatidyl choline and phosphatidyl ethanolamine was increased relatively slightly or not at all. Respiration was doubled. The "phospholipid effect" occurred in the microsom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

1961
1961
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(19 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…Polyphosphoinositides are present in large amount in myelin-rich particles of guinea pig forebrain (49). It has been suggested that inositol phospholipids in membrane have important roles in the selective control of movement of ions and other solutes, packaging and translocation of macromolecules, grouping and orientation of vectorially directed enzyme systems, and transmission of extracellular information to the cell interior (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphosphoinositides are present in large amount in myelin-rich particles of guinea pig forebrain (49). It has been suggested that inositol phospholipids in membrane have important roles in the selective control of movement of ions and other solutes, packaging and translocation of macromolecules, grouping and orientation of vectorially directed enzyme systems, and transmission of extracellular information to the cell interior (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the enzymatic activity in the vesicles of endothelial cells plays a specific role in the transport function of these structures. Whether this occurs through the activation or synthesis of vesicle membrane (39,40) with the participation of an ATP/ATPase energy-producing system or through some other parameter remains to be determined. However, it may be significant that the surface membrane of endo-BIBLIOGRAPHY…”
Section: Figurementioning
confidence: 99%
“…Yet the widespread occurrence of ACh and its associated enzymes in both neural and nonneural tissues suggests that its functions are not confined to this role. It has been proposed that ACh modifies ciliary movement in protozoans (Seaman and Houlihan, 1951) and in ciliated membranes of invertebrates (Bulbring, Burn and Shelley, 1953) and vertebrates (Kordik, Bulbring and Burn, 1952), acts as a local hormone in the control of excitability and contraction of smooth (Feldberg and Lin, 1950) and cardiac muscle (Burn and Kottegoda, 1953), is responsible for the initiation of the nerve action potential in axonal conduction (Nachmansohn, 1959), and regulates active or passive transfer of ions in the membranes of erythrocytes (Holland and Greig, 1950), frog skin (Kirschner, 1953), skeletal muscle (Van der Kloot, 1958), and avian salt glands (Hokin and Hokin, 1960). The evidence for and against these proposals has recently been summarised (Koelle, 1962b).…”
Section: VIImentioning
confidence: 99%